1984
DOI: 10.1210/jcem-59-1-170
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Granulosa Cell Aromatase Activity and Oocyte-Corona-Cumulus-Complex Maturity from Individual Human Follicles*

Abstract: The steroidogenic capability of granulosa cells isolated from 12 preovulatory human follicles was correlated with the stage of maturation of the corresponding oocyte-corona-cumulus-complex ( OCCC ). Individual follicles from human menopausal gonadotropin (hMG) stimulated cycles were aspirated 36 h after administration of hCG. Granulosa cells were cultured for 150 min and corresponding OCCC were evaluated for maturity before fertilization with human sperm. Granulosa cell aromatase activity was measured using 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…Therefore, it was confirmed that granulosa cells possess sufficient aromatase activity while shifting to a P-dominant situation at the ovulatory period. Also, in the human hMG-hCG cycle, it has been confirmed that granulosa cells sampled just after hCG injection have high aromatase activity (Dlugi et al 1984 ;Polan et al 1984).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it was confirmed that granulosa cells possess sufficient aromatase activity while shifting to a P-dominant situation at the ovulatory period. Also, in the human hMG-hCG cycle, it has been confirmed that granulosa cells sampled just after hCG injection have high aromatase activity (Dlugi et al 1984 ;Polan et al 1984).…”
Section: Discussionmentioning
confidence: 91%
“…Many factors that determine female fertility have yet to be examined in relation to paxillin. GC communications to oocytes can translate into oocyte quality: for example, aromatase activity in cumulus GCs has been linked to oocyte maturation in preovulatory follicles [71]. We have not yet investigated whether paxillin loss in GCs affects oocyte quality.…”
Section: Discussionmentioning
confidence: 99%
“…The human placental aromatase is located in the smooth endoplasmic reticulum and belongs t o the superfamily of monooxygenases. Aromatase has been found in reproductive gonads (Polan et al 1984;Rommerts et al 1982), placenta (Inkster and Brodie 1989), human skin fibroblasts, brain, and adipose tissue (Stillman et al 1990;Hutchison et al 1990;Lueprasitsakul and Longcope 1991). It has been suggested (Osawa and Igashiyawa 1984) that different aromatase enzymes might occur in different tissues since several estrogens are produced, namely estradiol-17P in ovary, estriol in placenta, and estrone in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%